PEMANFAATAN ALAT TANGKAP IKAN DARI RUMPON PADA NELAYAN DI DESA KUALA BUBON - Ayu Hasnita; Teuku Athaillah (LPPM Universitas Bina Bangsa, 2022)
The fisheries sector has a significant influence on the development of the Indonesian economy. Aceh waters have quite large potential for marine and fishery resources. The aim of empowering the Kuala Bubon village community is to help fishermen to be able to make the most of capture fisheries resources and integrate fishermen. The method of implementing community empowerment in the village of Kuala Bubon is carried out entirely in the field (offline). The activity of installing ijok FADs, starting from outreach to training on making ijok clumps and installing ijok FADs has been successfully carried out. This service is very useful for fishermen and adds to the knowledge of fishermen in catching fish